Ethics in applied linguistics research : language researcher narratives - De Costa, Peter I. (New York : Routledge, 2016)
'Explores how ethical issues are negotiated in different areas of language research, illustrating for graduate students in applied linguistics the ethical dilemmas they might encounter in the research methodology classroom and how they might be addressed. This volume serves to demystify the complex ethical decision-making process by its accounts of renowned researchers' ethical practices as they transpired on the ground and how they negotiated externally imposed research codes.'
Includes bibliographical references and index.
Keywords: Applied linguistics -- Research; Language and languages -- Study and teaching -- Moral and ethical aspects; Research -- Moral and ethical aspects